Country competitiveness in the era of globalization and the Fourth industrial revolution - Jovovic, Dusanka (Sociološki pregled, 2021)
An extremely complex nature of competition processes often makes the identification of the category of country competitiveness inaccurate and complicated to understand. This is particularly manifested in the era of globalization and the affirmation of the Fourth Industrial Revolution as two phenomena that shape contemporary developments in the world to a large extent. Globalization and the Fourth Industrial Revolution have ensured economic prosperity to some countries, but at the same time, they have also caused increasingly prominent developmental inequalities at worldwide level. The same conclusion refers to the matter of the competitiveness level achieved by the countries. This is convincingly proved by the 2019 World Economic Forum data about country competitiveness, based on which the greatest number of the countries in the world are still far from the targeted “limit” of competitiveness.